The Development of Body Movement Activity Program for Upper Elementary School Students - Dongkaew, Chokchai; Kanlueng , Tharin; Tanphanich , Theeranan (Asia Social Issues, 2025)
This study developed and evaluated a physical movement activity program for upper elementary students, focusing on three objectives: (1) program development, (2) improving learning capabilities, and (3) assessing its impact on knowledge, skills, and desirable characteristics. Conducted over eight weeks with three 50-minute sessions per week, the study involved 40 randomly selected students from 185 at Kasetsart University Laboratory School. Data analysis included validity and reliability testing, pre- and post-intervention comparisons, dependent t-tests, and descriptive statistics. Research instruments included a program manual (reliability = 0.82), knowledge and characteristics tests (difficulty index = 0.71, discrimination index = 0.41), and a skill test (reliability = 0.87, validity = 0.81). Results showed statistically significant improvements (p < 0.05) in knowledge and movement skills, along with enhanced self-confidence and teamwork. Quantitative analysis revealed increased average scores for both knowledge and physical movement skills post-intervention. This research highlights an engaging and challenging program that fosters physical movement and provides valuable insights for further refinement, ensuring continuous opportunities for students to develop their movement potential.